(untitled) (Journal of the College of Basic Education, 2023)
The aim of the present study was to evaluate the Antibacterial and healing enhancer activity of Calendula officinalis using different bacterial species and laboratory mice. It appears that there a significant increase P<0.05 in antibacterial activity of methanolic extract (hot and cold ) compared with standard antibiotic , especially in Klebsiella and E.coli. The results was showed significant p≥0.05dicreasing in the period healing in the group treated with extract and gentamycin ointment compared with paraffin wax,A better healing pattern with complete wound closure was observed in mice treated with Methanolic extract and gentamycin within 12 days, while the wound still opened in paraffin wax group . There was a significant reduction in wound area from day three onwards in treated mice Based on our results Calendula officinalis extracts have great potential as antibacterial compounds against wounds bacteria and they can be used in the treatment of infectious wounds, caused by multi-drug resistant strains and could be useful for developing alternative therapy for wounds infection